An Analytical Model for Compressive Creep Behavior of HDPE Used in Plastic Pipe Manufacturing - Sezer, S.; Ataoglu, S.; Gulluoglu, A. N.; Kadioglu, N. (TAYLOR & FRANCIS INC, 2008)
The creep behavior of high-density polyethylene has been studied by low compressive creep tests, and empirical results were analyzed and compared with analytically predicted results. The tests are performed upon ASTM standard specimens at various stress levels in the linear region. After these analyses, a mathematical model is derived and used to predict creep strain for long periods of time from the strain-time data obtained at different stresses over a time interval of 24h.
Keywords: Burgers method; Creep; High-density polyethylene; Linear viscoelasticity; Modeling; Polymer Science